The relationship of diverse leisure activities with flourishing - Mock, Steven E.; Smale, Bryan (Frontiers in Psychology, 2023)
The relationship between leisure and wellbeing is of great interest in the field of leisure studies. Keyes (2002) developed a typology of flourishing vs. languishing that encompasses subjective, psychological, and social wellbeing and is linked with physical health and functioning. However, little research has been done to show how participation in various forms of leisure might be associated with this flourishing typology. Drawing on data from community data with over 5,000 adult participants, we assessed how leisure is associated with a flourishing typology. For the present analyses, we focus on scales that assessed social leisure (e.g., socializing with friends), cultural leisure (e.g., festival attendance), home-based leisure (e.g., reading books for pleasure), physically active leisure (e.g., moderate or vigorous), and media-based leisure (e.g., time spent playing computer games or watching TV). A flourishing typology was constructed from single-item ratings on life satisfaction (subjective wellbeing), psychological well-being (self-perceptions that one’s life activities are worthwhile), and social wellbeing (sense of belonging). Flourishing was linked to greater participation in cultural, social, home-based, and physically active leisure. Greater time spent playing computer games and watching TV was associated with languishing. Thus, certain forms of leisure reflect flourishing and others are linked with languishing. The nature of these associations remains to be explored, in particular, whether leisure contributes to flourishing or if flourishing facilitates certain forms of leisure participation.